Targeting HMGB1-NFκb Axis and miR-21 by Glycyrrhizin: Role in Amelioration of Corneal Injury in a Mouse Model of Alkali Burn - Wang, Peihong; Hao, Peng; Chen, Xi; Li, Linghan; Zhou, Yongying; Zhang, Xiaohan; Zhu, Lin; Ying, Ming; Han, Ruifang; Wang, Liming; Li, Xuan (Frontiers in Pharmacology, 2022)
Corneal neovascularization (CNV) is a sight-threatening condition usually is associated with various inflammatory settings including chemical injury. High mobility group box 1 (HMGB1) is identified as an inflammatory alarmin in diverse tissue damage. Here, we evaluate the expression of HMGB1 and the consequences of its inhibition through its selective inhibitor glycyrrhizin (GLY) in alkali burn-induced corneal inflammation and neovascularization. GLY effectively attenuated alkali burn-induced HMGB1 expression at both mRNA and protein levels. Furthermore, slit-lamp analysis, ink perfusion, H&E staining, and CD31 histochemical staining showed that GLY relieved corneal neovascularization, while GLY attenuated VEGF expression via inhibiting HMGB1/NF-κB/HIF-1α signal pathway. In addition, GLY treatment decreased the cytokine expression of CCL2 and CXCL5, accompanied by the reduction of their receptors of CCR2 and CXCR2. GLY diminished the inflammatory cell infiltration of the cornea, as well as reduced the expression of IL-1β, IL-6, and TNF-α. Moreover, treatment with GLY reduced the degree of cornea opacity through inactivating extracellular HMGB1 function, which induced TGF-β1 release and myofibroblast differentiation. Furthermore, we found that GLY treatment attenuated the upregulation of miR-21 levels in alkali burned cornea; while inhibition of miR-21in keratocytes in vitro, significantly inhibited TGF-β1-induced myofibroblast differentiation. Collectively, our results suggested that targeting HMGB1-NFκb axis and miR-21 by GLY could introduce a therapeutic approach to counter CNV.